The Influence of Entrepreneurial Characteristics, Entrepreneurship Orientation, Entrepreneurship Competence on Organizational Capability and Business Performance (Survey of Micro Small and Medium Enterprises in Bajawa District, Ngada Regency, East Nusa Tenggara) - Wis Kurniawati Sene; Edy Yulianto; Mohammad Iqbal (Wacana Journal of Social and Humanity Studies, 2019)
This research is based on background by the influence of entrepreneurial characteristics, entrepreneurial orientation, entrepreneurial competence on organizational capability and business performance in Bajawa District, Ngada Regency, East Nusa Tenggara. Data collection in this study uses a questionnaire method distributed to 122 respondents, using a simple random method with Proportional Random Sampling allocation. While the analysis technique is done using Partial Least Square. The results showed that Entrepreneurial characteristics had a positive influence on Organizational Capability with a path coefficient of 0.2143. Entrepreneurship Orientation has a positive influence on Organizational Capability with a path coefficient of 0.2534. Entrepreneurship Competence has a positive influence on Organizational Capability with a path coefficient of 0.4117. Entrepreneurial characteristics have a positive influence on Business Performance with a path coefficient of 0.2087. Entrepreneurship Orientation has a positive influence on Business Performance with a path coefficient of 0.203. Entrepreneurship competencies have a positive influence on Business Performance with a path coefficient of 0.2061. Organizational capability has an influence on Business Performance with a path coefficient of 0.2932. These results indicate that entrepreneurial characteristics, entrepreneurial orientation, entrepreneurial competencies possessed by MSMEs owners in Bajawa Subdistrict can improve the organizational capabilities and performance ofMSMEs.